Levels of von Willebrand factor antigen and von Willebrand factor cleaving protease (ADAMTS13) activity predict clinical events in chronic heart failure - Gombos, Tímea; Makó, Veronika; Cervenak, László; Papassotiriou, Jana; Kunde, Jan; Hársfalvi, Jolán; Förhécz, Zsolt; Pozsonyi, Zoltán; Borgulya, Gábor; Jánoskuti, Lívia; Prohászka, Zoltán (Thrombosis and Haemostasis, 2009)
Decreased activity of ADAMTS13, the von Willebrand factor (VWF) cleaving protease, was recently reported in cardiovascular diseases and in hepatic failure. Chronic heart failure (CHF) is characterised by abnormalities of left ventricular function accompanied by the failure of the liver and dysregulation of endothelial activation. Therefore, the aim of our study was to measure ADAMTS13 activity in CHF, and determine the prognostic value of VWF and ADAMTS13 on major clinical events in CHF.ADAMTS13 activity (measured by FRETS-VWF73 substrate) was decreased in CHF (n = 152, left ventricular ejection fraction <45%), and it correlated negatively with B-type natriuretic peptide (BNP) NYHA (New York Heart Association) classes, markers of synthetic capacity of the liver and endothelial dysfunction (all p<0.005). Both, high VWF:Ag levels (hazard ratio [HR] 1.52, 95% confidence interval [CI] 1.189–1.943), and low ADAMTS13/VWF:Ag ratios (HR 0.70, 95% CI 0.58–0.84) independently and significantly predicted short-term (1 year followup) clinical adverse events in heart failure (HF).Decreased activity of ADAMTS13 with concomitant high VWF:Ag levels is a significant independent predictor of clinical events in CHF. The levels of the two molecules may integrate the impaired synthetic capacity of the liver and the disturbed endothelial regulation and can therefore be a useful tool to predict clinical events in CHF.
Keywords: Heart failure; ADAMTS13; von Willebrand factor; endothelial dysfunction; hepatic failure